Inggris - Mardiyah Mardiyah; M. Yunus Abu Bakar (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
An efforts needs to be taken by a nation to improve education in pursuing advancement and developments in science and technology. We are currently entering the period of the Industrial Revolution 4.0 and the Era of Society 5.0, in which it is necessary for people to use creativity and technology to solve social problems. The goal of this discussion is to identify the most relevant HR supervision theories for the Industrial Revolution 4.0 and the Society 5.0 eras in order to raise the standard of instructors by requiring them to understand technology. This research was carried out using the library research method which consisted of determining the theme of the discussion, finding reference sources according to the theme of the discussion, compiling the contents of the material, and concluding the results of several reference articles. The theory applied was the relationship between the HR supervision function and teacher quality in the era of the industrial revolution 4.0 and the era of society 5.0. The results of the discussion indicate the need for renewal. Education and training need to be packaged into an activity that is able to improve mindsets, new innovations, as well as teachers' mastery of technology in schools, so as to create modern learning according to the needs of the times.